Religious men and masculine identity in the Middle Ages - Cullum, P. H.; Lewis, Katherine J., 1969- (Gender in the Middle Ages, 2013)
"The complex relationship between masculinity and religion, as experienced in both the secular and ecclesiastical worlds, forms the focus for this volume, whose range encompasses the rabbis of the Babylonian and Palestinian Talmud, and moves via Carolingian and Norman France, Siena, Antioch, and high and late medieval England to the eve of the Reformation. Chapters investigate the creation and reconstitution of different expressions of masculine identity, from the clerical enthusiasts for marriage to the lay practitioners of chastity, from crusading bishops to holy kings. They also consider the extent to which lay and clerical understandings of masculinity existed in an unstable dialectical relationship, at times sharing similar features, at others pointedly different, co-opting and rejecting features of the other; the articles show this interplay to be far more complicated than a simple linear narrative of either increasing divergence, or of clerical colonization of lay masculinity. They also challenge conventional historiographies of the adoption of clerical celibacy, of the decline of monasticism and the gendered nature of piety."--Back cover